EFEKTIVITAS PERASAN DAUN AGERATUM CONYZOIDES L. TERHADAP PERTUMBUHAN JAMUR TRICHOPHYTON RUBRUM - Iqbal Firdaus; Diah Sudiarti (JURNAL BIOSHELL, 2018)
Plants have a variety of function one of them as a medicine. Ageratum conyzoides L. plant efficacious as antimicrobial. This study aims to determine the effectiveness the leaf juice of Ageratum conyzoides L. on the growth of Trichophyton rubrum fungus. This research was conducted invitro using dilution method and hole method, and using Randomized Complete Design with three repetitions. The results will be analyzed using Anova Test, followed by Duncan test. Based on the results of analysis it is known that the leaf juice of Ageratum conyzoides L has the inhibitory power to the growth of Trichophyton rubrum. Minimum constraint concentration (KHM) of Ageratum conyzoides L leaf extract on Trichophyton rubrum growth was present at concentration of 40% with mean diameter of 1.61 cm resistance zone. So it can be concluded that the leaf juice of Ageratum conyzoides L is effective against Trichophyton rubrum growth, because it can inhibit its growth.Keywords: Ageratum conyzoides L., effectiveness, MIC, Trichophyton rubrum